Evaluation of the Environmental Performance of Seasonal Spaces in the Vernacular Architecture of the Regions With Cold Climate: A Case Study in Ardabil - Marjaneh Kharrat Sadeghi; Mahsa Javadi Nodeh; Mehrdad Sarabi (Journal of Advances in Environmental Health Research)
Background: Attention to climatic elements has played a crucial role in fostering harmony between the built environment and nature. Incorporating these elements into the design of modern buildings not only enhances the health and well-being of occupants but also helps mitigate anthropogenic environmental pollution. In this context, the present study aims to examine the environmental performance of various spaces in the vernacular architecture of Ardabil across cold and hot seasons. The objective is to identify climate-responsive strategies that contribute to reducing energy consumption and minimizing environmental pollution. Methods: To this end, two traditional houses in Ardabil were studied using a data logger. Data collection was carried out through field observations and logical reasoning, followed by numerical analyses to evaluate the environmental performance of the structures. Results: The results indicated that the temperature of the indoor spaces in these houses was at least 10.45 °C higher than that of the outdoor spaces during the cold months of the year. Conclusion: The application of climate-responsive strategies, particularly passive solar designs during winter, in the construction of traditional houses was estimated to reduce CO₂ emissions by 218.47 kg and natural gas consumption by 82.07 kg per month for every 100 m² of space during the cold seasons. In contrast, during the hot seasons, while indoor temperatures in most spaces exceeded outdoor temperatures, they remained within the acceptable range of human thermal comfort.